Agbacha Ekuru Nwa Dance: A Study of Performance Ethics for Music Students in Colleges of Education - Nwauzor, Uzoma Hyacinth (Journal of Education and Practice, 2021)
performances and providing the theoretical framework for the study of general music education by students in colleges of education. To promote the baseline from which dance performance is produced to enhance cultural heritage and the structure with which all aspects of social events are finally understood. The need for increased awareness and participation in dance is apparent. In tertiary institutions, the study of dance as an academic course virtually does not exist. Dance should be given the attention it deserves in the curriculum for the promotion of sustainable development in creating jobs for the youths. Methodology: Participant observation-adopting this survey is very necessary due to the nature of the research, it is a practical performance that involved dance groups. There are varieties of approaches to research in any field of investigation. Using the descriptive method is aimed at obtaining information concerning the current status of Agbacha ekuru nwa dance as it is expressed in the traditional setting. This is important in understanding the dance similarities among the groups selected from each of the 3 local government areas in Mbaise. The data collected for this project are obtained through oral interviews, observation, personal contact, and participation. Observation and participation in dance rehearsal are very necessary for future performance with the students. Uzoigwe (1998) explained that the descriptive method allows for better acceptance and understanding of all music elements discovered during research. Results: Traditional dance is a part of life evolution, memory, and history, it is integral with the communities of the peoples' culture. And because communities re-shape and re-model folk music in line with changing tradition, ideals, and social interaction, it should be used to educate the people on the ills and goodwill of the society. Given the multiplicity of social performances in Nigeria, it will be possible to agree that the people's total culture is subsumed with music and dance and that it has become very important in promoting and developing our cultural heritage. Unique contribution to theory, practice and policy: There is the need for us to revive our cultural heritage by ensuring that those subjects which teach and safeguards morals, norms and value system are given attention in school curriculum to revamp the fallen standard of education, cultural ideologies, and judgment regarding the way we see ourselves. This will lead to a drastic change in our attitude and behaviour. To better attract the interest of learners, the curriculum has a part to play; this is by designing a solid structure for the dance program in all levels of education in Nigerian schools. The nature of dance, as well as students' interest, will be captured and aimed at revitalizing general music education in our schools providing a balance between intellectual tasks and social interaction. This will be a way of expanding knowledge and skills for future use as a form of integrating cultural heritage into our educational system. Using Agbacha ekuru nwa dance as a case study will be beneficial to students because if all organizational principles are applied to teaching and learning it will provide structured performance ethics towards achieving collective objectives. Dance is teamwork and should be organized as such. One of the benefits is creativity in performance; talent development could be formed where students, lovers of music, and the larger society can function very well in creating dance. This will be one of the most valuable courses to enhance human personality.